Ambergris - VanderMeer, Jeff (MCD, Farrar, Straus and Giroux, 2020)
"Before Area X, there was Ambergris. Jeff VanderMeer conceived what would become his first cult classic series of speculative works: the Ambergris Trilogy. Now, for the first time ever, the story of the sprawling metropolis of Ambergris is collected into a single volume, including City of Saints and Madmen, Shriek: An Afterword, and Finch"--